Palm Frond with Its Throat Cut - Vertiz, Vickie (Book collections on Project MUSE., 2017)
"A poetry collection that offers a glimpse into LA Latina life, exploring the history and lexicon of a queer Chicana, her family, and her passions"--Provided by publisher.